2020
DOI: 10.1055/s-0040-1715616
|View full text |Cite
|
Sign up to set email alerts
|

Facelift Surgery: History, Anatomy, and Recent Innovations

Abstract: Facelift surgery has become a beautifully predictable, safe, and extremely effective operation. Our patients can expect natural and long-lasting results as a direct outcome of our improved understanding and applications of surgical facial anatomy. Rhytidectomy, once an operation of simple well-placed elliptical skin excisions, evolved to include longer skin flaps, skin and platysma flaps with various superficial muscular aponeurotic system (SMAS) manipulations, and various deep plane techniques involving the s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
12
0
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 20 publications
(13 citation statements)
references
References 47 publications
0
12
0
1
Order By: Relevance
“…Although the term superficial musculoaponeurotic system (SMAS) was first coined by Mitz and Peronie under the supervision of Tessier in 1976, 6–8 the layer is believed to have been originally described by Sir Charles Bell as early as 1799. 8 Attention to this layer and its handling by Skoog is what resulted in a paradigm shift for facelift surgery.…”
Section: Introductionmentioning
confidence: 99%
“…Although the term superficial musculoaponeurotic system (SMAS) was first coined by Mitz and Peronie under the supervision of Tessier in 1976, 6–8 the layer is believed to have been originally described by Sir Charles Bell as early as 1799. 8 Attention to this layer and its handling by Skoog is what resulted in a paradigm shift for facelift surgery.…”
Section: Introductionmentioning
confidence: 99%
“…Commensurate with improved understanding in facial anatomy and greater societal acceptance, surgical face-lifts have evolved over time from a procedure shrouded in mystery to one that is generally safe, reproducible, and effective. 16 Accordingly, the International Society of Aesthetic Plastic Surgery reported face-lifts as the 10th most common aesthetic surgical procedure performed worldwide in 2019 with 448,485 cases, which represents a 9% increase from 2015. 17 Currently, even with the ongoing COVID situation, studies have shown that interest in aesthetic procedures, in general, are on the rise 18 and analysis of social media platforms, such as Twitter, has confirmed that interest in “face-lifts” increased significantly post declaration (March 2020) of the current pandemic by the World Health Organization.…”
Section: Discussionmentioning
confidence: 99%
“…Surgeons quickly became unsatisfied with the results and began to perform extended subcutaneous undermining. 2,3 Skoog operated on the deeper layer, which was later named SMAS by Mitz and Peyronie. 4,5 This technique has become the foundation of the modern facelift.…”
Section: Discussionmentioning
confidence: 99%
“…The early facelift merely cut a piece of skin. Surgeons quickly became unsatisfied with the results and began to perform extended subcutaneous undermining 2,3 . Skoog operated on the deeper layer, which was later named SMAS by Mitz and Peyronie 4,5 .…”
Section: Discussionmentioning
confidence: 99%